Faunistic Composition Of Phasmids At Santubong National Park, Sarawak - Isma Syafiqah, Ismail (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study was focused on the diversity and abundance of phasmids at Santubong National Park. This research has been conducted for 12 days, starting from 17 January 2015 until 25 January 2015 and 27° February 2015 until 29" February 2015. Transect line were used to sample the phasmids which were captured by bare hand and aerial net (flying phasmid). A total of 116 individuals were captured comprising of 14 species that has been identified and thus, this research has successfully updated the species diversity of phasmids (H'= 1 93) in Santubong National Park. These individuals represent the four families of Phasmida known as Aschiphasmatidae, Bacillidae, Heteronemiidae, and Phasmatidae The highest relative abundance of family is Heteronemiidae (60%), followed by the family of Bacillidae (27%), Phasmatidae (7%) and Aschiphasmatidae (7%). The most dominant species that has been found are Acacus sarawacus (35 individuals), followed by Hoploclonia gecko (28 individuals)